Familiale Tradierungsprozesse in einer Drei-Generationen-Perspektive Kontinuierliche Veränderungen - veränderliche Kontinuitäten - Radicke, Christina (Universitätsverlag Göttingen, 2014)
In this qualitative study, familial mediation and appropriation processes are examined in a three-generation perspective, taking into account the in-family development of social development processes in two neighboring subregions. Attention is given not only to the continuity, but also to the adaptations and changes of the forms and content of family traditioning. The linking of a generational perspective with Halbwachs' considerations of collective memory opens up several comparison options. In addition to capturing familial, generational and regional similarities and differences, the dynamics of familial tradition can be worked out in this way.